2019
DOI: 10.1029/2018jf004716
|View full text |Cite
|
Sign up to set email alerts
|

Field and Numerical Investigation of Transport Mechanisms in a Surface Storage Zone

Abstract: In‐stream surface storage zones (SSZs) caused by lateral recirculation areas play a significant role in the transport and fate of contaminants in rivers. Lateral recirculating areas have long residence times that favor nutrient uptake, accumulation of pollutants, and interactions with reactive sediments. In watersheds affected by acid‐mine drainage, SSZs have profound effects on biogeochemical processes, controlling the local concentration and distribution of toxic elements along the channel. Despite the impor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
38
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(41 citation statements)
references
References 57 publications
3
38
0
Order By: Relevance
“…The natural cavities play a major role in water ecology as they constitute favorable sites for fauna and flora developments. The supply of dissolved and suspended substances to the cavity, such as nutrients, gazes, and pollutants (Sanjou et al, 2018;Sandoval et al, 2019), occurs by mass transfer across the mixing layer at the interface between the cavity and the main stream. Besides, the fluvial and coastal harbors are major infrastructures for navigation and commercial activities, for which continuity of operations is crucial for the economy.…”
Section: A Contextmentioning
confidence: 99%
“…The natural cavities play a major role in water ecology as they constitute favorable sites for fauna and flora developments. The supply of dissolved and suspended substances to the cavity, such as nutrients, gazes, and pollutants (Sanjou et al, 2018;Sandoval et al, 2019), occurs by mass transfer across the mixing layer at the interface between the cavity and the main stream. Besides, the fluvial and coastal harbors are major infrastructures for navigation and commercial activities, for which continuity of operations is crucial for the economy.…”
Section: A Contextmentioning
confidence: 99%
“…We assumed that the solute exchange rate between mobile and immobile zones (Λ, /s) was first-order, which implies that solute residence times are approximately exponential in the mobile zone. Sandoval et al, 2019). Such a truncated power law is quite flexible in the range of behaviours it can represent, including the compound influences of a hierarchy of exponential zones (e.g.…”
Section: Solute Transportmentioning
confidence: 99%
“…Willmann et al, 2008), which have been shown to exist in streams and rivers (e.g. Sandoval et al, 2019). To minimise model degrees of freedom, we fixed the power-law slope (β = 0.75) and allowed V, D, Λ, and τ T to freely vary.…”
Section: Solute Transportmentioning
confidence: 99%
“…The flow past a lagoon (deep zone) creates a shear layer at the interface between the flow and the deep zone which is characterized by the highest transport of momentum. In low aspect depth ratios, a main vortex dominates the flow (Jackson et al, 2013; Ouro et al, 2020; Sandoval & Mignot, 2019), while in high aspect depth ratios other secondary rotating structures can be formed. The secondary vortex is reported to increase the residence time of the flow within the deep zone (Jackson et al, 2013).…”
Section: Introductionmentioning
confidence: 99%